Safety and effectiveness of switching to Abacavir/Lamivudine plus rilpivirine for maintenance therapy in virologically suppressed HIV-1 individuals in Singapore (SEALS) - Lim, Z. C. (BioMed Central Ltd, 2022)
10.1186/s12981-021-00402-7